Activity of free radical oxidation processes in rats with paracetamol hepatitis and correction with shiitake mushrooms thick extract - І. І. Herasymets; L. S. Fira; І. І. Medvid (The State Expert Center of the Ministry of Health of Ukraine, 2021)
The antioxidant defense system controls and inhibits all stages of free radical formation reactions, which start from their initiation and end with the formation of hydroperoxides and malonic dialdehyde. Disorders of the body's antioxidant defense system can be caused by both endogenous and exogenous factors and can lead to the oxidative stress development. For the purpose of the negative impact minimizing and correction of the existing disorders, both natural and synthetic origin antioxidants are used. Preference is given to antioxidants of natural origin, due to their mild action and minimal side effects. Shiitake mushrooms are known in China and Japan as a product that has nutritional and medicinal value, for thousands of years. They contain an extremely rich complex of various biologically active substances that can have antioxidant, hepatoprotective effect and influence on the liver diseases pathogenesis. The aim of the work was to investigate the effect of shiitake mushrooms thick extract on the activity of free radical processes and indicators of the antioxidant system under the conditions of paracetamol hepatitis in rats. The experimental work was being conducted on the white male rats, which were divided into 10 groups of 6 animals each. Acute hepatitis was simulated by intragastric administration of paracetamol in a dose of 1 250 mg/kg 1 time per day (for 2 days) as a suspension in 2% starch gel solution. We investigated the effect of shiitake mushrooms thick extract on the induced pathology, which was administered intragastrically 2 hours before the paracetamol introduction and daily after the lesion in a dose of 150 mg/kg of the rat's body weight. Silibor was selected as the comparison drug, which was administered according to the same scheme like the investigated extract in a dose of 20 mg/kg of the animal's body weight. Euthanasia was conducted on the 3rd, 7th and 10th day after the onset of the lesion. Liver homogenate and animal serum were examined. The effectiveness of shiitake mushrooms thick extract was evaluated under the conditions of the caused pathology by superoxide dismutase and catalase activity, as well as by the content of TBA-active and proteins oxidative modification products. An increasing of the TBA-active products content and the products of proteins oxidative modification in the serum and liver of animals after the toxic paracetamol exposure testifies to the liver damage and the development of acute hepatitis in rats. Decreased activity of antioxidant enzymes such as catalase and superoxide dismutase was also noted. An investigation, which was conducted by us, allowed us to reveal a positive effect of shiitake mushrooms thick extract on the activity of lipoperoxidation and oxidative modification of proteins under the conditions of white rats paracetamol lesion.